DIGITALIZATION OF TAX ADMINISTRATION IN THE REPUBLIC OF UZBEKISTAN: THEORETICAL FOUNDATIONS, INTERNATIONAL EXPERIENCE, AND FISCAL EFFECTIVENESS (International Congress on Economics, Management and Business Studies, 2026)
This paper analyzes the theoretical foundations, international experience, and national practice of digitalizing tax administration in the Republic of Uzbekistan. The fiscal effectiveness of the taxpayers’ personal cabinet (my.soliq.uz), the electronic invoicing system (EIS), online cash registers (OCR), and AI-based risk assessment systems is examined. A comparative analysis with the advanced experiences of South Korea, Estonia, and Brazil is conducted. The findings indicate that the introduction of digital tools serves as a key factor in expanding the taxpayer base, narrowing the tax gap, and reducing administrative costs. At the same time, issues of digital literacy among small businesses and the rural population, cybersecurity, and institutional capacity remain relevant.
Keywords: Tax administration, digital economy, tax gap, electronic invoicing, online cash registers, my.soliq.uz, fiscal effectiveness, tax reform, digitalization.